Comparative examination of a bacterium preparation (BACTOFIL® A10) and an artificial fertilizer [CA(NO3)2] on calcareous chernozem soil - Tállai, Magdolna (Acta Agraria Debreceniensis, 2010)
In a small-pot experiment a bacterium preparation, Bactofil® A10 and an artificial fertilizer containing Ca(NO3)2 in different dosages were studied on calcareous chernozem soil, concerning the readily available nutrient content of soil (nitrate-nitrogen, AL-phosphorus, ALpotassium content of soil, some soil microbial characteristics (total number of bacteria and fungi, cellulose-decomposing and nitrifying bacteria, CO2-production of soil), and the amount of the plant biomass.The readily available nutrient content of the calcareous chernozem soil increased due to the treatments, except for the change in the soil nitrate-nitrogen content, which did not measure up to the control due to the effect of high-dosage Bactofil.The treatments also influenced the examined microbial characteristics of the soil positively. The artificial treatments significantly increased the total number of bacteria and the number of cellulose-decomposing and nitrifying bacteria. The low-dosage Bactofil significantly increased the number of cellulose-decomposing bacteria and both Bactofil dosage significantly increased the number of nitrifying bacteria. The measure of the soil respiration grew in all treatments, but significantly only in Ca(NO3)2 fertiliser treatments.The quantity of the plant biomass was grew in a low-dosage Bactofil and significantly in the artificial fertiliser treatments. The highest plant biomass quantity was measured in the high-dosage artificial fertiliser treatment.In the correlation analyses we found some medium positive correlation between the soil chemical, microbiological parameters examined, and the plant biomass in the case of both treatment-forms. Based on our results Ca(NO3)2 artificial fertiliser treatments on calcareous chernozem soil proved to be more stimulating regarding theexamined soil characteristics and the amount of the plant biomass, but the low-dosage Bactofil also positively influenced the majority of thesoil characteristics examined in terms of nutrient supply.